The Meaning of Using the Empty Instagram Feed Trend among University Students in Tanjungpinang City - Puspita Ramayanti; Marisa Elsera; Nanik Rahmawati (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Instagram is one of the most popular social media among young people today. The use of Instagram is usually a means to show self-existence and social life. However, the phenomenon of using empty Instagram feeds among users, especially among students, provides new meaning and views in the use of Instagram social media. The purpose of this study is to explain the meaning of the phenomenon of using empty Instagram feeds among students in Tanjungpinang city. The method used in this study uses a descriptive-qualitative method which examines the meaning of using empty Instagram feeds among students in Tanjungpinang city using a purposive sampling technique with 5 informants, namely students who use empty Instagram feeds. The theoretical basis used is Herbert Blummer's theory of symbolic interactionism. Based on the results of the study, the researcher.. Found that the symbol of emptiness in an empty Instagram feed was not only considered a trend by its users but as a result of a reflection of the meaning and expression of the self-doubt of several informants who had bad experiences as victims of bullying or skimming, as a form of restriction. the flow of globalization that creates life without privacy, as well as a new way to create an image in the formation of self-identity.